1961
DOI: 10.1128/jb.81.5.733-740.1961
|View full text |Cite
|
Sign up to set email alerts
|

Fission-Product and Cerium Uptake by Bacteria, Yeasts, and Molds

Abstract: The metabolism of rare earths and of other significant components of fission products by microorganisms during growth is largely undescribed. A few important specialized studies are available. Both stable lanthanum (Richards and Troutman, 1940) and cerium (Miller, 1959) are known to accumulate in yeast cells, and yeast ' This work was performed at the Medical Division, Oak Rtidge Institute of Nuclear Studies, Oak Ridge, Tennessee, tunder contract with the U. S. Atomic Energy Commission. We therefore compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1968
1968
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…In fact, uptake can vary widely within specific genera, i.e. Streptomyces flavovirens has been shown to take up >75% of added cerium while S. viridoflavus collects <25% (Johnson and Kyker 1961). It has been argued that such uptake is largely passive (Johnson and Kyker 1961), but others have found that microbes can actively oxidize cerium (Moffett 1990).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, uptake can vary widely within specific genera, i.e. Streptomyces flavovirens has been shown to take up >75% of added cerium while S. viridoflavus collects <25% (Johnson and Kyker 1961). It has been argued that such uptake is largely passive (Johnson and Kyker 1961), but others have found that microbes can actively oxidize cerium (Moffett 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Streptomyces flavovirens has been shown to take up >75% of added cerium while S. viridoflavus collects <25% (Johnson and Kyker 1961). It has been argued that such uptake is largely passive (Johnson and Kyker 1961), but others have found that microbes can actively oxidize cerium (Moffett 1990). This result, coupled with the finding that REEs control the expression and activity of MeDH in methanotrophs, and that most of the added REEs are associated with biomass, however, suggest an uptake mechanism for REEs exists in at least some microbes.…”
Section: Discussionmentioning
confidence: 99%
“…Microbial mass leaving the rumen with the particulate matter would most likely be associated with the small digesta particles, for which the kinetic pattern would more closely resemble that of Yb infused intraruminally. In addition, microorganisms are known to have a high affinity for rare-earth elements (Johnson and Kyker, 1961), and high concentrations of Yb (and Ce) in bacterial pellets isolated from ruminal contents have been reported (Combs et al, 1992;. Thus, the true outflow rate of the microbial mass in the rumen may not differ significantly from the dilution rate of an extrinsic marker, such as Yb, infused intraruminally.…”
mentioning
confidence: 99%
“…The magnitude of radiocerium sedimented from rumen contents was surprisingly large in view of the relatively low centrifugal forces employed, which would not have sedimented many bacterial species, and the possibility of soluble complex formation by cerium with colloidal macromolecules such as protein or soluble complexing molecules. The latter possibility is exemplified by the investigation of Johnson and Kyker (1961). These investigators added radiocerium (molarity not stated) to nutrient broth media inoculated with different bacteria.…”
Section: Resultsmentioning
confidence: 99%